2019
DOI: 10.3168/jds.2019-16520
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular docking study of novel cholesterol esterase inhibitory peptides from camel milk proteins

Abstract: Novel bioactive peptides from camel milk protein hydrolysates (CMPH) were identified and tested for inhibition of cholesterol esterase (CEase), and their possible binding mechanisms were elucidated by molecular docking. Papain-generated CMPH showed the highest degree of hydrolysis. All CMPH produced upon enzymatic degradation demonstrated a dramatic enhancement of CEase inhibition compared with intact camel milk proteins, with papain-generated hydrolysate P 9 displaying the highest inhibition. Peptide identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 35 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…Cholesterol esterase has been reported to be associated with the development of obesity and other related complications. Thus, in an interesting study conducted by Mudgil et al (2019), novel peptides were isolated from camel milk protein hydrolysate and then evaluated for their inhibition of cholesterol esterase. Results revealed that hydrolysate obtained by the digestion with papain exhibited the highest degree of hydrolysis.…”
Section: -15mentioning
confidence: 99%
“…Cholesterol esterase has been reported to be associated with the development of obesity and other related complications. Thus, in an interesting study conducted by Mudgil et al (2019), novel peptides were isolated from camel milk protein hydrolysate and then evaluated for their inhibition of cholesterol esterase. Results revealed that hydrolysate obtained by the digestion with papain exhibited the highest degree of hydrolysis.…”
Section: -15mentioning
confidence: 99%
“…These outcomes are similar to those reported by ( Nagaoka et al, 2001 ) who had previously reported the number of residues in hypocholesterolemic peptides ranges from 5 to 20. ( Baba et al, 2021 ) and ( Mudgil et al, 2019a ) have also recently reported a similar number of amino acid in the identified peptides which were predicted to possess CEase and PL inhibitory properties. Moreover, peptides (GGV, IVG, and VGVL) from the Amaranth protein reported by Soares et al (2015) demonstrated inhibition of HMG-CoA reductase enzyme, which implies a promising hypocholesterolemic effect.…”
Section: Resultsmentioning
confidence: 71%
“…Amongst the identified bioactive peptides from APHs, peptide FPFVPAPT could establish a bond with two amino acid residues present in the catalytic triad (Ser 194 and His435), and Ala108, and Phe324 which are part of an active site residue of CEase suggesting the strong inhibitory potential of this peptide against CEase. The peptides that could bind the residues of Phe324 and His435 are particularly gaining attention as CEase inhibitors, as previously reported in bioactive peptides derived from camel milk protein hydrolysates ( Mudgil et al, 2019a ) and camel whey protein hydrolysates ( Baba et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations